Upper semi-continuity of the Hilbert–Kunz multiplicity. (2nd February 2016) - Smirnov, Ilya
Abstract : We prove that the Hilbert–Kunz multiplicity is upper semi-continuous in F-finite rings and algebras of essentially finite type over an excellent local ring.